1993
DOI: 10.1207/s15326888chc2202_3
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Preterm Infants at 3 Years of Age: Parental Response to the Presence of Developmental Problems

Abstract: In this article we describe developmental status at 3 years and family utilization of early intervention services of 24 children who were born prematurely and weighed less than 1,500 g or who required mechanical ventilation at birth. Findings indicated (a) a low rate of major disabling conditions; (b) a high rate of developmental, mild cognitive, and behavioral concerns; and (c) a lack of family follow-through on referrals for early intervention services for potentially responsive children, even though the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…These findings are consistent with a large literature describing problematic underutilization of services, particularly among individuals with low incomes and people of color (Huber et al, 1993;Meisels, 1989;Palfrey et al, 1989;Stauber & Mahan, 1987). The reality that only a small percentage of the participants reported ever having used parenting support services raises concerns about the effectiveness of parenting services in reaching the low-income, African American parents of babies at high risk for developmental delays and in need of extra support during their infants' early years.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with a large literature describing problematic underutilization of services, particularly among individuals with low incomes and people of color (Huber et al, 1993;Meisels, 1989;Palfrey et al, 1989;Stauber & Mahan, 1987). The reality that only a small percentage of the participants reported ever having used parenting support services raises concerns about the effectiveness of parenting services in reaching the low-income, African American parents of babies at high risk for developmental delays and in need of extra support during their infants' early years.…”
Section: Discussionsupporting
confidence: 91%
“…However, the effectiveness of formal interventions and parenting programs often is compromised because these services are not used (Meisels, 1989;Stauber & Mahan, 1987). One study found that only one-sixth of families with premature infants were receiving adequate early intervention services three years after the premature delivery (Huber, Holditch-Davis, & Brandon, 1993). This underutilization remains a major challenge in early intervention practice, and contributes to social and economic costs that are likely to compound in future years (Arcia, Serling, & Gallagher, 1992;Halpern, 1990).…”
Section: W K Kellogg Foundationmentioning
confidence: 99%
“…The barriers to parenting created by the NICU environment and parents’ emotional reactions to the environment may negatively influence the parent–infant relationship and the infant's long‐term developmental outcome (Affleck & Tennen 1991, Huber et al. 1993, Singer et al.…”
Section: Introductionmentioning
confidence: 99%
“…1999). The postponement of parenting results in extended emotional and psychological stress that can lead to parents not being emotionally attached to their infant at the time of discharge, and may contribute to greater parenting risk and child vulnerability (Affleck & Tennen 1991, Huber et al. 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The postponement of parenting and the emotional and psychological stress, may cause parents not being able to emotionally connect to their infant at time of discharge, and may contribute to greater parenting risk and child vulnerability [24,53,54]. These findings highlight the importance of therapeutic interventions during hospitalisation in the NICU aiming at improvement of parent-infant interactions and early parental- therapeutic support focusing on the psychological impact after premature birth.…”
Section: Introductionmentioning
confidence: 99%